1997
DOI: 10.1074/jbc.272.15.10021
|View full text |Cite
|
Sign up to set email alerts
|

Absence of an Unusual “Densely Methylated Island” at the Hamster dhfr ori-β

Abstract: An unusual "densely methylated island" (DMI), in which all cytosine residues are methylated on both strands for 127-516 base pairs, has been reported at mammalian origins of DNA replication. This report had far-reaching implications in understanding of DNA methylation and DNA replication. For example, since this DMI appeared in about 90% of proliferating cells, but not in stationary cells, it may regulate origin activation. In an effort to confirm and extend these observations, the DMI at the well characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Similar, diverse, non-symmetric sites of methylation have been described previously as "densely methylated islands" at origins of replication associated with ribosomal protein S14 and the dhfr locus in Chinese hamster ovary cells (33). However, it has been suggested that these densely methylated islands of methylated cytosine residues might be artifactual, arising from incomplete denaturation of the DNA prior to treatment with sodium bisulfite, at least at the dhfr locus (34). In the present experiments, it is unlikely that the unusual pattern of methylation arises from incomplete denaturation of the DNA.…”
Section: Discussionsupporting
confidence: 62%
“…Similar, diverse, non-symmetric sites of methylation have been described previously as "densely methylated islands" at origins of replication associated with ribosomal protein S14 and the dhfr locus in Chinese hamster ovary cells (33). However, it has been suggested that these densely methylated islands of methylated cytosine residues might be artifactual, arising from incomplete denaturation of the DNA prior to treatment with sodium bisulfite, at least at the dhfr locus (34). In the present experiments, it is unlikely that the unusual pattern of methylation arises from incomplete denaturation of the DNA.…”
Section: Discussionsupporting
confidence: 62%
“…The bisulfite method requires denaturing double-stranded DNA and bisulfite treatment for 4-18 h, followed by sequencing, microarray detection, or methylation-specific PCR 71 and their variations. 72 Some problems arising from these approaches are: (a) DNA occasionally partially degrades; 73 (b) incomplete bisulfite reactions result in false positives; 74 (c) resulting singlestranded DNA adopts alternate folded conformations 75 that prevent PCR amplifications; (d) primer design becomes problematic in methylation-specific PCR; and (e) microarray detection technologies are expensive. 76 Many of the above artifacts can be solved 77 with appropriate changes in experimental conditions, however the total time for this reaction and analysis is long and remains constant.…”
Section: Seer-lacmentioning
confidence: 99%
“…Chromosomal DNA was extracted and cleaved with restriction enzymes to eliminate the possibility that subsequent purification of nascent Br-DNA retrieved c-myc sequences whose origin may not have fired but were connected to an active, BrdUrd-labeled origin located some distance away. Nascent Br-DNA was affinity-purified and analyzed for m CpGs using the bisulfite method as described previously (27). An example of these data is shown in Fig.…”
Section: Some Replicationmentioning
confidence: 99%
“…A strong signal from methylated DNA (indicated by cytosine residues in the C lane at the positions of CpG dinucleotides) was evident within 1 min of pulse labeling, whereas the signal from Closed lollipops denote methylated cytosines at CpG dinucleotides that were determined using four independent methods, including the bisulfite method (24,27). Nine of these m CpGs are clustered within a 356-bp region (shaded box) adjacent to the OBR that was defined by the transition between discontinuous and continuous DNA synthesis (55).…”
Section: Some Replicationmentioning
confidence: 99%
See 1 more Smart Citation